Doctor who? Developing a translation device for exploring successful doctoral being and becoming - Clarence, Sherran; van Heerden, Martina (Critical Studies in Teaching and Learning, 2023)
Doctoral training and education tends to focus on how to research and write a thesis, which can take many forms. However, a thesis is not the only valued outcome of a doctorate: the emerging Doctor is important too. Being and becoming a Doctor implies identity work and engaging affective dimensions of researcher development alongside researching and writing a thesis. These are not always explicit in doctoral education, though. Thus, we contend that their role in researcher development needs to be named, described, and understood. In this paper we use Constellations from Legitimation Code Theory to make visible two valued doctoral attributes and dispositions as exemplars. We have used published papers in the field of doctoral studies as data. Within increasingly diverse doctoral student cohorts, it is important to actively foreground the development of valued affective dispositions through doctoral education to enable more candidates to achieve success in their doctorates.